(untitled) (Community Based Medical Journal, 2024)
Ovarian fibrothecomas comprise tumors in the spectrum of ovarian sex cord / stromal tumors where there are components of both an ovarian fibroma and an ovarian thecoma. They account for 3-4% of all ovarian tumors. Most occur in adult women, with 65% in postmenopausal women. However, it represents only 2% of pediatric ovarian tumors. They are the most common benign solid ovarian tumor. The tumors are usually hormonally inactive but can be estrogenic or sometimes androgenic. Here we are reporting a rare case of a 15-year-old girl presenting with primary amenorrhea, severe hirsutism and finally diagnosed with ovarian fibrothecoma. After surgical removal of the tumor, a dramatic response was observed as the patient developed menarche. She was relieved of her hirsutism by laser therapy later, but her deep voice remained the same. CBMJ 2024 January: vol. 13 no. 01 P: 95-97